Poverty issues in Sri Lanka : towards new empirical evidence - Symposium on Poverty Research in Sri Lanka 2002 : Colombo, Sri Lanka); Centre for Poverty Analysis (Sri Lanka); Program to Improve Capacities for Poverty Research; Sri Lanka Association for the Advancement of Science; Konrad-Adenauer-Stiftung.; Deutsche Gesellschaft für Technische Zusammenarbeit ([Colombo] : The Centre, 2003)
Contributed articles presented at third annual Symposium on Poverty Research in Sri Lanka held in Colombo in August 2002.
Subtitle on cover: towards new empirical insights.
Keywords: Poverty -- Sri Lanka -- Congresses